Challenges and prospects of e-procurement in public sector in Bangladesh: A study on Health Engineering Department (HED) under Ministry of Health and Family Welfare, Bangladesh - Rahman, Md. Taifur (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020.